Potential of bovine kappa - casein as biomarker for detection of adulteration of goat's milk with cow's milk - Jamnik, Polona (Array, 2019)
Using two-dimensional (2-D) electrophoresis it was shown that bovine kappa-casein could be an appropriate biomarker of adulteration of goat’s milk with cow’s milk not only in raw milk, but also for milk thermally processed by pasteurization or treated with ultra-high-temperature. The presence of cow’s milk in goat’s milk was detected at level of 2 %. Furthermore, position of bovine kappa-casein spots on 2-D gels remained unchanged even with samples from two different geographical origins, Belgium and Slovenia. These results show that neither thermal processing nor different geographical area seem to affect the position of bovine kappa-casein spots on 2-D gels.